2015
DOI: 10.5455/2320-6012.ijrms20150313
|View full text |Cite
|
Sign up to set email alerts
|

The success rate of CPR and its related factors in the emergency department of Ardabil Imam Khomeini hospital, 2013

Abstract: Cardiopulmonary resuscitation is one of the greatest achievements in the history of medicine and quick intervention to prevent death or postponing sudden cardiac arrest in someone. CPR includes an organized action which was made in patients with cardiopulmonary arrest. CPR an attempt to keep the circulatory and respiratory systems artificially, so that enough oxygen to keep vital organs supplied and physiological activity of spontaneous circulation return to normal status. 1 CPR plays an important role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
2
4
1
Order By: Relevance
“…The prevalence of opioids poisoning in 71 (55%) male children was higher than that in their female counterparts with 58 cases (45%). The obtained data are in line with the studies conducted by Elahimehr et al [18], Haresabadi et al [23], and Farzaneh and associates [7]. Various studies in other countries also reported that the number of poisoned male children was more than the number of female children [24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The prevalence of opioids poisoning in 71 (55%) male children was higher than that in their female counterparts with 58 cases (45%). The obtained data are in line with the studies conducted by Elahimehr et al [18], Haresabadi et al [23], and Farzaneh and associates [7]. Various studies in other countries also reported that the number of poisoned male children was more than the number of female children [24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…Farnaghi et al also documented that 31 male and female children with methadone poisoning were admitted to Loghman-Hakim Hospital [1]. However, the present study data are inconsistent with those of Farzaneh et al [7], Cheraghali et al [17], Elahimehr et al [18], and Farnaghi and colleagues [1].…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations